Tradisi Dan Transformasi Menelusuri Sejarah Perkembangan Ilmu Politik - zariah, ainun; Handayani, Nadia; Zein, M. Zilalul Qur’an (Lembaga Riset dan Publikasi, 2026)
Political science can be simply defined as the science that studies politics. The main objective of this study is to provide a comprehensive overview of the history of the development of political science. This study is useful as an academic reference for understanding the roots and development of political science. This study uses literature studies. This approach focuses on the dynamics of the development of political science from time to time. The results of this study indicate that political science has developed from a normative approach in classical times to a more empirical and rich in multidisciplinary perspectives in the contemporary era. The journey of political science as a scientific discipline shows complex dynamics and continues to develop in line with changing times.